2017
DOI: 10.1016/j.molcel.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cockayne’s Syndrome A and B Proteins Regulate Transcription Arrest after Genotoxic Stress by Promoting ATF3 Degradation

Abstract: Cockayne syndrome (CS) is caused by mutations in CSA and CSB. The CSA and CSB proteins have been linked to both promoting transcription-coupled repair and restoring transcription following DNA damage. We show that UV stress arrests transcription of approximately 70% of genes in CSA- or CSB-deficient cells due to the constitutive presence of ATF3 at CRE/ATF sites. We found that CSB, CSA/DDB1/CUL4A, and MDM2 were essential for ATF3 ubiquitination and degradation by the proteasome. ATF3 removal was concomitant wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 62 publications
6
102
0
Order By: Relevance
“…In CSB-deficient cells, however, the ATF3 protein and ATF3 occupancy at its target promoters remain high (64). This work suggested that CSB might be required to remove ATF3 from its target promoters to allow transcription resumption (Figure 2), and this hypothesis was subsequently tested (53). It was found that CSB collaborates with Cockayne syndrome protein A (CSA) to promote the ubiquitination and degradation of ATF3, thereby allowing transcription to resume (Figure 2).…”
Section: Csb In Transcription Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In CSB-deficient cells, however, the ATF3 protein and ATF3 occupancy at its target promoters remain high (64). This work suggested that CSB might be required to remove ATF3 from its target promoters to allow transcription resumption (Figure 2), and this hypothesis was subsequently tested (53). It was found that CSB collaborates with Cockayne syndrome protein A (CSA) to promote the ubiquitination and degradation of ATF3, thereby allowing transcription to resume (Figure 2).…”
Section: Csb In Transcription Regulationmentioning
confidence: 99%
“…However, CSB contains a ubiquitin-binding domain (UBD) in its C-terminal region, which is absent in its yeast homologs (Figure 1). This domain is suggested to be critical for CSB function in TC-NER as well as transcription (52,53) and is likely specific to CSB’s role in multicellular organism development.…”
Section: Regulation Of Csb’s Biochemical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional dysregulation upon UV irradiation is also observed in XP‐B/CS and XP‐G/CS cells, although apparently not related to Sirt1 impairment . Interestingly, it has been recently shown that UV irradiation persistently arrests transcription of about 70% of genes in CS patient cells defective in either CSA or CSB, because of the constitutive presence of the ATF3 repressor …”
Section: Molecular Basis Of Overlap Syndromesmentioning
confidence: 98%
“…54 Interestingly, it has been recently shown that UV irradiation persistently arrests transcription of about 70% of genes in CS patient cells defective in either CSA or CSB, because of the constitutive presence of the ATF3 repressor. 55 An additional model suggests that the molecular alterations under- Mitochondria function as the "powerplant" of the cells and supply ATP by oxidative phosphorylation, a process that induces the production of high levels of ROS. As a consequence, mitochondrial DNA (mtDNA) is constantly exposed to oxidative stress leading to damage accumulation.…”
Section: In Mammalian Cells Excision Repairmentioning
confidence: 99%